A New Framework for Collaborative Ontology Construction for an Agricultural Domain from Heterogeneous Information Resources. Issue 3 (3rd July 2018) - Zhitomirsky-Geffet, Maayan; Mograbi, Chaim Z.
ABSTRACT: In this paper, we present and evaluate a new event-based ontology model and methodology that enables multilingual, domain-specific ontology construction for an agricultural domain by experts and non-expert users. Twenty-six non-expert users were guided to collaboratively populate an ontology and create cross-resource relationships based on expert guidelines and using the developed new graphical tool and data from the existing online agricultural databases. The study's results show that the accuracy of the ontology built using the graphical tool, as well as the non-expert user satisfaction with the tool, was substantially higher than that of the state-of-the-art, collaborative WebProtégé.